A conceptual perspective of internal audit quality and local government performance in Nigeria - Usang, Obal Usang Edet; Salim, Basariah (2015)
The study highlights the influence of internal audit quality on the performance of an organization.Internal audit quality components such as competence, quality of internal audit work, objectivity and independence, training and development, and management support for the internal audit function are critical for enhancing organizational processes.It relies on extant literature in developing the conceptual framework and arriving at hypotheses that guide the study. Thus, the study suggests that the quality of internal audit influences performance and this link opens up a new perspective in examining the local government performance in Nigeria.